Optimization of the Inorganic Salts in Coenzyme Q10 Fermentation Medium of Rhodobacter sphaeroides Based on Uniform Design and Artificial Neural Network and Genetic Algorithm - Yi Zheng; Yujun Xiao; Shuling Tang; Junpeng Li; Yingzi Wu; Yong Zhou (Fermentation, 2025)
Coenzyme Q10 (CoQ10) has attracted widespread attention in recent years due to its momentous physiological functions. Microbial fermentation is the major method in CoQ10 industrial production, and Rhodobacter sphaeroides is the main strain for the production of CoQ10 by fermentation. Optimization of the culture medium is a popular solution to improve the metabolite production. Culture medium is the material basis for microbial growth and product synthesis, of which inorganic salts are a key ingredient. Uniform design (UD), artificial neural network (ANN), and genetic algorithm (GA) are the main research methods. Through uniform design (UD) and artificial neural network/genetic algorithm (ANN-GA) progressive optimization, an optimal formulation of the inorganic salts in fermentation medium was obtained (g·L−1): MgSO4 12, NaCl 2.5, FeSO4 1.6, KH2PO4 0.8, MnSO4 0.1, CaCl2 0.1. Ultimately, the fermentation yield of CoQ10 could reach 255.36 mg·L−1. ANN-GA exhibited a superior prediction capability compared to UD. Compared to UD, the optimization results of ANN-GA had a smaller relative error (ANN-GA 1.23%; UD 3.01%) and a higher increase rate in the fermentation level of CoQ10 (ANN-GA 4.1%; UD 2.04%). R. sphaeroides had a high demand for Mg2+.